Vascular Complications During Catheter Ablation of Cardiac Arrhythmias: A Comparison Between Vascular Ultrasound Guided Access and Conventional Vascular Access. (9th August 2016) - SHARMA, PARIKSHIT S.; PADALA, SANTOSH K.; GUNDA, SAMPATH; KONERU, JAYANTHI N.; ELLENBOGEN, KENNETH A.
Ultrasound Guided Vascular Access for Electrophysiologic Procedures: Introduction: Vascular access related complications are the most common complications from catheter based EP procedures and have been reported to occur in 1–13% of cases. We prospectively assessed vascular complications in a large series of consecutive patients undergoing catheter based electrophysiologic (EP) procedures with ultrasound (US) guided vascular access versus conventional access. Methods and Results: Consecutive patients undergoing catheter ablation procedures at VCU medical center were included. US guided access was obtained in all cases starting June 2015 (US group) while modified Seldinger technique without US guidance (non‐US group) was used in cases prior to this date. All vascular complications were recorded for a 30‐day period after the procedure. A total of 689 patients underwent 720 procedures. Ablations for ventricular tachyarrhythmias (ventricular tachycardia: VT, premature ventricular contractions: PVCs) accounted for 89 (12%) cases; atrial fibrillation (AF) ablations accounted for 328 procedures (46%) and other catheter based procedures accounted for 42% of cases. A significantly higher incidence of complications was noted in the non‐US group compared with the US group (19 [5.3%] vs. 4 [1.1%], respectively, P = 0.002). Major complications were also higher among the non‐US group (9 [2.5%] vs. 2 [0.6%], P = 0.03). Increasing age (P = 0.04) and non‐US guided vascular access (P = 0.002) were associated with a higher risk of vascular access complications. Conclusion: In a large series of patients undergoing catheter based EP procedures for cardiac arrhythmias, US guided vascular access was associated with a significantly decreased 30‐day risk of vascular complications.